Level of physical activity and smoking in undergraduate students - Rodrigues, Elizângela Sofia Ribeiro; Cheik, Nadia Carla; Mayer, Anamaria Fleig (Revista de Saúde Pública, 2008)
OBJECTIVE: To evaluate the level of physical activity in undergraduate students and to investigate its potential association with smoking. METHODS: A cross-sectional study with a stratified sample proportional to the total number of students was carried out in Gurupi, Central-West Brazil, in 2005. The sample comprised 871 subjects. The IPAQ-8 short version was applied to assess the level of physical activity. Smoking status was evaluated by a modified World Health Organization (WHO) questionnaire and the magnitude of smokers' nicotine dependence was quantified using the Fagerström nicotine dependence scale. The frequencies, prevalences and prevalence ratios were determined by Yates' chi-square test or Fisher's exact test in the entire sample and stratified by area, course, shift and gender, with a 5% statistical significance level. RESULTS: Mean age was 25 years old (SD±8) and mean age at first smoking experience was 17 years old (SD±4). The prevalence of physical inactivity and smoking was 29.9% and 7.2%, respectively. The overall prevalence of sedentary smokers and non-smokers was 8.5%, and 91.5%, respectively, but the difference was not statistically significant. A higher prevalence of smoking and physical inactivity was found in those over 25 (48.6%, p